Transcranial sonography in differential diagnosis of Parkinson disease and other movement disorders. Issue 14 (20th July 2021) - Wang, Li-Shu; Yu, Teng-Fei; Chai, Bin; He, Wen
Abstract: Background: Reports evaluating the efficacy of transcranial sonography (TCS) for the differential diagnosis of Parkinson disease (PD) and other movement disorders in China are scarce. Therefore, this study aimed to assess the application of TCS for the differential diagnosis of PD, multiple system atrophy (MSA), progressive supranuclear palsy (PSP), and essential tremor (ET) in Chinese individuals. Methods: From 2017 to 2019, 500 inpatients treated at the Department of Dyskinesia, Beijing Tiantan Hospital, Capital Medical University underwent routine transcranial ultrasound examination. The cross-sections at the midbrain and thalamus levels were scanned, and the incidence rates of substantia nigra (SN) positivity and the incidence rates of lenticular hyperechoic area were recorded. The echo of the SN was manually measured. Results: Of the 500 patients, 125 were excluded due to poor signal in temporal window sound transmission. Among the 375 individuals with good temporal window sound transmission, 200 were diagnosed with PD, 90 with ET, 50 with MSA, and 35 with PSP. The incidence rates of SN positivity differed significantly among the four patient groups ( χ 2  = 121.061, P  < 0.001). Between-group comparisons were performed, and the PD group showed a higher SN positivity rate than the ET ( χ 2  = 94.898, P  < 0.017), MSA ( χ 2  = 57.619, P  < 0.017), and PSP ( χ 2  = 37.687, P  < 0.017) groups. SN positivity showed a good diagnostic value for differentiating PD from the other three movement diseases, collectively or individually. The incidences of lenticular hyperechoic area significantly differed among the four patient groups ( χ 2  = 38.904, P  < 0.001). Next, between-group comparisons were performed. The lenticular hyperechoic area was higher in the PD group than in the ET ( χ 2  = 6.714, P  < 0.017) and MSA ( χ 2  = 18.680, P  < 0.017) groups but lower than that in the PSP group ( χ 2  = 0.679, P  > 0.017). Conclusion: SN positivity could effectively differentiate PD from ET, PSP, and MSA in a Chinese population.